Amputation neuroma derived from a remnant cystic duct 30 years after cholecystectomy: A case report. (2019) - Hirohata, Ryosuke; Abe, Tomoyuki; Amano, Hironobu; Kobayashi, Tsuyoshi; Shimizu, Akinori; Hanada, Keiji; Yonehara, Shuji; Nakahara, Masahiro; Ohdan, Hideki; Noriyuki, Toshio
Highlights: Amputation neuroma (AN) arising from a remnant cystic duct after cholecystectomy is rare. It is difficult to distinguish AN and malignant tumor because radiological findings of ANs mimic findings of malignancy. Intraoperative diagnosis is necessary to select an appropriate surgical procedure. Abstract: Introduction: Amputation neuroma is difficult to diagnose preoperatively. Amputation neuroma arising from a remnant cystic duct after cholecystectomy is rare. Herein, we present a case of amputation neuroma derived from a remnant cystic duct along with a review of the literature. Presentaion of the case: A 60-year-old woman visited our hospital due to a tumor located in the hepatoduodenal ligament. A gallbladder adenoma was resected by open cholecystectomy 30 years prior. Endoscopic ultrasonography demonstrated branched intraductal papillary mucinous neoplasm of the pancreas and a tumor with a low-echoic pattern in the extrahepatic biliary system. Enhanced computed tomography revealed a 6-mm tumor in the artery phase. Surrounding lymph nodes were not swollen. Magnetic resonance cholangiopancreatography showed that the tumor presented with slightly high intensity on T2 weighted imaging. Operative findings revealed that the whitish nodule was moderately attached to surrounding tissues. The remnant cystic duct and the tumor could not be separated; however, no direct invasion toward common bile duct was observed. Rapid intraoperative pathological examination demonstrated that the tumor was a neuroma. The peration time was 251 min and blood loss was 80 ml. The patient was discharged nine days after surgery with no postoperative complications. Conclusion: It is difficult to distinguish amputation neuroma from malignant tumors because radiological findings of a neuroma mimic findings of malignancy. Intraoperative diagnosis is necessary to select an appropriate surgical procedure due to the difficulty of preoperative diagnosis.